2010
DOI: 10.1016/j.tim.2009.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial outer membranes: in search of proteins

Abstract: SummaryThe cell wall is a major virulence factor of Mycobacterium tuberculosis and contributes to its intrinsic drug resistance. Recently, cryo-electron microscopy showed that the mycobacterial cell wall lipids form an unusual outer membrane. Identification of the components of the uptake and secretion machinery across this membrane is critical for understanding the physiology and pathogenicity of M. tuberculosis and for the development of better anti-tuberculosis drugs. Although the genome of M. tuberculosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
139
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 205 publications
(147 citation statements)
references
References 103 publications
(134 reference statements)
7
139
0
1
Order By: Relevance
“…Why does M. tuberculosis possess such a unique and sophisticated "ménage à trois"? The presence of a distinct outer membrane and a remarkably large number of putative outer membrane proteins in M. tuberculosis (18) suggests that this bacterium could make use of a functional export chaperone under certain circumstances. The fact that Rv1957 possesses key predicted structural elements of the E. coli SecB chaperone that are necessary for its interaction with preproteins and with its SecA partner at the Sec translocon (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Why does M. tuberculosis possess such a unique and sophisticated "ménage à trois"? The presence of a distinct outer membrane and a remarkably large number of putative outer membrane proteins in M. tuberculosis (18) suggests that this bacterium could make use of a functional export chaperone under certain circumstances. The fact that Rv1957 possesses key predicted structural elements of the E. coli SecB chaperone that are necessary for its interaction with preproteins and with its SecA partner at the Sec translocon (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Functions in protein translocation have not been described for any of these putative SecB-like proteins, and no SecB homologs have been found in mycobacteria. Despite their classification as Gram-positive bacteria, recent discoveries have shown that there is a well-defined outer membrane in mycobacteria (15,16) and that Mycobacterium tuberculosis encodes a significant number of putative outer membrane proteins (17,18). How these outer-membrane proteins are assisted in the cytoplasmic space and targeted to the inner membrane in these bacteria remains unknown.…”
mentioning
confidence: 99%
“…Such an approach may lead to a new class of anti-infectives that could sensitize pathogens to host immune responses by inhibiting bacterial defense mechanisms as recently described by Carl Nathan and colleagues (27). Targeting MctB might be a promising strategy because the surface accessibility of MctB (28) may enable putative inhibitors to reach its target directly without the need to cross the notoriously impermeable outer membrane of Mtb, a major determinant of intrinsic drug resistance (29).…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a handful of proteins have been suggested to be outer membrane proteins (15), but their functions have not been confirmed by phenotypes of the corresponding mutants of M. tuberculosis. This study, to our knowledge, represents the first example in which the phenotype of a gene deletion mutant-that is, an uptake defect for a small molecule-corresponds with the channel-forming activity of a purified M. tuberculosis protein.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, proteins secreted by M. tuberculosis need to cross both an inner and an outer membrane (14), a barrier of notoriously low permeability in M. tuberculosis (15). However, the only known secretion systems capable of translocating proteins across both M. tuberculosis membranes are the type VII secretion systems encoded by esx operons.…”
mentioning
confidence: 99%